TransLatin Joyce Global Transmissions in Ibero-American Literature - Price, B.; Price, B.; Salgado, C.; Salgado, C.; Schwartz, J.; Schwartz, J. (Literatures of the Americas,, 2014)
TransLatin Joyce explores the circulation of James Joyce's work in the Ibero-American literary system. The essays address Joycean literary engagements in Spain, Portugal, Argentina, Mexico, and Cuba, using concepts from postcolonial translation studies, antimodernism, game theory, sound studies, deconstruction, and post-Euclidean physics.